2017
DOI: 10.1002/ejhf.1045
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between heart failure, concurrent chronic obstructive pulmonary disease and beta‐blocker use: a Danish nationwide cohort study

Abstract: Carvedilol prescription carried an increased hazard of HF hospitalization and lower restricted mean persistence time among patients with COPD and concurrent HF. Additionally, we found a widespread phenomenon of carvedilol prescription at variance with the European Society of Cardiology guidelines and potential for improving the proportion of patients treated with β-blockers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…SENIORS showed that nebivolol (beta1-blocker, NO-releasing activity) is an effective and well-tolerated treatment for HF in elderly patients regardless of ejection fraction [33][34][35], a subgroup analysis showed nebivolol was less effective in those patients with diabetes [36], and the benefits of nebivolol appeared to be related to the maintenance dose achieved [37]. Nebivolol users had a lower HHF than carvedilol users among concurrent HF and chronic obstructive pulmonary disease patients [38]. Nebivolol might improve cardiac function in HFrEF patients [39], but it did not improve exercise capacity in patients with HFpEF [40].…”
Section: Nebivololmentioning
confidence: 99%
See 1 more Smart Citation
“…SENIORS showed that nebivolol (beta1-blocker, NO-releasing activity) is an effective and well-tolerated treatment for HF in elderly patients regardless of ejection fraction [33][34][35], a subgroup analysis showed nebivolol was less effective in those patients with diabetes [36], and the benefits of nebivolol appeared to be related to the maintenance dose achieved [37]. Nebivolol users had a lower HHF than carvedilol users among concurrent HF and chronic obstructive pulmonary disease patients [38]. Nebivolol might improve cardiac function in HFrEF patients [39], but it did not improve exercise capacity in patients with HFpEF [40].…”
Section: Nebivololmentioning
confidence: 99%
“…Pharmacotherapy Tolvaptan TACTICS-HF [8], AQUAMARINE [9,10], Shirakabe et al [11], EVEREST [12], SECRET, QUEST, METEOR [13] Ivabradine SHIFT [14,15], INTENSIFY, ETHIC-AHF, Bagriy et al [17], CARVIVA HF [18] Sacubitril/valsartan PARADIGM-HF [19][20][21][22][23], PIONEER-HF [24,25], EVALUATE-HF [26], TRANSITION [27,28], PARAMOUNT [29,30], PARAGON-HF [31] Nebivolol SENIORS [33][34][35][36][37], Sessa et al [38], Brehm et al [39], ELANDD [40], CARNEBI [41] Levosimendan LIDO [42], SURVIVE [43], REVIVE [44], LevoRep [45], Zhang et al [46], LION-HEART [47], LEAF [48], Jia et al [49], LAICA [50], Leo-DOR [51] MRA Eplerenone: EPHESUS [75], EMPHASIS-HF [52][53][54][55]…”
Section: Treatments Key Trialsmentioning
confidence: 99%
“…Indeed, in practice, there are often challenges with uptitrating therapies, especially medications with potential for hypotension and renal dysfunction side effects, and in patients with co‐morbid conditions such as chronic obstructive pulmonary disease (COPD). Oftentimes there is concern regarding beta‐blockers in this population given the increased risk of hospitalization for COPD with beta‐blocker use, especially non‐selective beta‐blockers such as carvedilol . Studies show that patients with HF and COPD are prescribed all HF medications at a lower rate than those without COPD, however the discrepancy is most pronounced with beta‐blockers …”
Section: Doses Used In Clinical Practicementioning
confidence: 99%
“…Oftentimes there is concern regarding beta-blockers in this population given the increased risk of hospitalization for COPD with beta-blocker use, especially non-selective beta-blockers such as carvedilol. 39 Studies show that patients with HF and COPD are prescribed all HF medications at a lower rate than those without COPD, however the discrepancy is most pronounced with beta-blockers. 40 In dedicated HF disease management programmes and studies utilizing standardized protocol for medication dosing, it has been suggested a majority of patients can achieve target dosing.…”
Section: Doses Used In Clinical Practicementioning
confidence: 99%
“…This debate may be fuelled anew by the publication of a large Danish heart failure cohort, presented in this issue of the Journal . Though not intended as the main research question and only investigated in patients also having chronic obstructive pulmonary disease (COPD), the risk of heart failure‐related hospitalization was significantly higher with carvedilol compared with the selective β‐blockers bisoprolol, metoprolol, and nebivolol, even after multivariable adjustment.…”
mentioning
confidence: 99%